Inhibition of microRNA-495 Enhances Therapeutic Angiogenesis of Human Induced Pluripotent Stem Cells. (9th September 2016) - Liang, Jialiang; Huang, Wei; Cai, Wenfeng; Wang, Lei; Guo, Linlin; Paul, Christian; Yu, Xi-Yong; Wang, Yigang
Abstract : Therapeutic angiogenesis has emerged as a promising strategy to regenerate the damaged blood vessels resulting from ischemic diseases such as myocardial infarction (MI). However, the functional integration of implanted endothelial cells (ECs) in infarcted heart remains challenging. We herein develop an EC generation approach by inhibiting microRNA-495 (miR-495) in human induced pluripotent stem cells (hiPSCs) and assess the angiogenic potential for MI treatment. The anti-angiogenic miR-495 belonging to Dlk1-Dio3 miR cluster was identified through expression profiling and computational analysis. Loss-of-function experiments for miR-495 were performed using a lentiviral transfer of antisense sequence in hiPSCs. The pluripotency of hiPSCs was not impacted by the genetic modification. Induced with differentiation medium, miR-495 inhibition enhanced the expression of EC genes of hiPSCs, as well as the yield of ECs. Newly derived ECs displayed prominent angiogenic characteristics including tube formation, cell migration, and proliferation. Mechanistically, miR-495 mediated the expression of endothelial or angiogenic genes by directly targeting vascular endothelial zinc finger 1. After transplantation in immunodeficient MI mice, the derived ECs significantly increased neovascularization in the infarcted heart, prevented functional worsening, and attenuated expansion of infarct size. The functional integration of the implanted ECs into coronary networks was also enhanced by inhibiting miR-495. miR-495 represents a new target not only for promoting EC generation from hiPSCs but also for enhancing angiogenesis and engraftment of hiPSC-derived ECs in ischemic heart.